Behavioral and immune changes in v-HA-ras transgenic mice - Colombo, Lucas Luis (2000)
Transgenic mice (Oncomice) with an activated v-Ha-ras oncogene under the control of the mouse mammary tumor virus promoter develop mammary tumors. We wondered if the expression of the v-Ha-ras oncogene product would induce changes in mice behavioral activity, that could be associated with alterations in their immune system. Behavior was evaluated in an open field study considering line crossings and rears. Oncomice consistently showed less activity than FVB mice. Lieber-DeCarli diet decreased both types of activity in both strains. Cocaine treatment increased line crossings in both strains. Oncomice spleen and thymus cell supernatants contained higher levels of IL-2. Oncomice serum had higher levels of IL-1α. Our results suggest a direct association between higher levels of IL-1α and lower open field activity. Therefore, we can infer that the increased level of IL-1α found in Oncomice, could have a key role in oncogene induced immune and behavioral changes, and could be a requirement to facilitate its transforming activity.